Pair living emerged early in placental mammals - Sam F. Walmsley; Charlotte-Anaïs Olivier; Adrian V. Jaeggi; Lindelani Makuya; Jordan S. Martin; Loren D. Hayes; Carsten Schradin (Proceedings of the National Academy of Sciences, 2026)
It is widely assumed that the first placental mammals were solitary. Here, we tested this assumption and which ecological and life history factors are related to mammalian social organization. We compiled a comprehensive database by reviewing over 14,000 primary peer-reviewed publications on the social organization of the 5,390 extant placental mammal species. We found empirical data for 726 species across 1,473 populations: 353 populations were primarily solitary, 250 populations pair living, and 870 populations group living. Notably, 367 species (51%) and 583 populations (40%) exhibited intraspecific variation in social organization. Using a Bayesian phylogenetic framework that incorporates intraspecific variation, we show that the ancestral placental mammal was mainly but not exclusively solitary, displaying intraspecific variation. Pair living was estimated to account for approximately 26% of ancestral social organization. Phylogeny explained most of the variation between species, while life history and ecology were less important. Our analysis found that the ecology and life history of extant solitary and pair-living mammals is very similar and different from those of group-living mammals. Our results revise prevailing theories of mammalian social evolution, revealing that pair living emerged early, shifting the focus of studying mammalian social evolution from the origins of pair living to the origins of group living.